Pengaruh Disiplin dan Motivasi Terhadap Kinerja Guru SMK Plus Umar Zahid - Mohammad Saiq Ali Sya’bana; Moh. Ja’far Sodiq Maksum (Management and Education Journal, 2026)
This study aims to analyze the influence of discipline and work motivation on teacher performance at SMK Plus Umar Zahid, a vocational school integrated with a pesantren-based education system. Using a quantitative correlational design, the research involved 46 teachers selected through a saturated sampling technique. Data was collected using a Likert-scale questionnaire and tested for validity and reliability, yielding valid items with Cronbach's Alpha values above 0.70. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination (R²). The results show that discipline has a positive but insignificant effect on teacher performance, while motivation has a positive and significant effect. Simultaneously, both variables significantly influence performance, with an R² value of 0.506, indicating that 50.6% of performance variation is explained by discipline and motivation. The findings highlight the dominant role of intrinsic and extrinsic motivation in enhancing teacher performance, strengthened by the religious and communal values of the pesantren environment. This study contributes to understanding human resource management in Islamic-based vocational education and provides recommendations for enhancing teacher professionalism through integrated strategies involving motivation, discipline, and organizational support.